2020
DOI: 10.1186/s13213-020-01549-w
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of a new Verminephrobacter eiseniae strain: a nephridial symbiont of earthworms

Abstract: Purpose: Verminephrobacter is a genus of symbiotic bacteria that live in the nephridia of earthworms. The bacteria are recruited during the embryonic stage of the worm and transferred from generation to generation in the same manner. The worm provides shelter and food for the bacteria. The bacteria deliver micronutrients to the worm. The present study reports the genome sequence assembly and annotation of a new strain of Verminephrobacter called Verminephrobacter eiseniae msu. Methods: We separated the sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Also, the organs such as skin have a rich population of symbiotic microbes. We extracted the whole genome of Verminephrobacter eiseniae from the draft genome of E. fetida and published a paper [ 8 ]. Hence, we examined the hundreds of Gram-stained tissue sections of the prostate gland and checked them for the presence of any microbes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the organs such as skin have a rich population of symbiotic microbes. We extracted the whole genome of Verminephrobacter eiseniae from the draft genome of E. fetida and published a paper [ 8 ]. Hence, we examined the hundreds of Gram-stained tissue sections of the prostate gland and checked them for the presence of any microbes.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of 28 genes in purine metabolism and 19 genes in pyrimidine metabolism indicates the importance of the pathways. It has been reported that the symbiotic bacteria of Eisenia fetida was able to synthesize vitamin B2, thiamine, biotin, propionate, pyruvate, folate, and pantothenate and may provide to the worm [ 8 ]. In E. eugeniae, pathways for the metabolism of all these metabolites except propionate were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA fragments were purified from the agarose gel using the Genei clean purification technique (Genei Gel Extraction Kit). According to the instructions, the Miniprep Kit (Genei) has been used to obtain pure super-coiled plasmid DNA with excellent yield (35μl) (Arumugaperumal et al, 2020;Garcia Jr et al, 2020;.…”
Section: Methodsmentioning
confidence: 99%